Problems of ecological movement development in the Republic of Kazakhstan (International relations and international law Journal, 2016)
Environmental problems cannot be considered without taking into account environmental movements, itsemergence, development, role and significant value in solution of ecological problems. Environmental movement is very important element to increase the civil society role in formation of the state ecological policy. The authors consider various aspects of activities ecological associations and non-governmental organizations, also state projects in Kazakhstan; make an attempt to give the analysis to the events held for improvement of an ecological situation, and also prove the need of reforming this sector in order to increase the efficiency of undertaken measures. The authors conclude the article with possible mechanisms of a larger involvement of citizens and increase the efficiency of NGO’s activity in the ecological sphere.
Keywords: Kazakhstan; environmental movement; ecological problems; NGO; «green economy»; social movements